2011
DOI: 10.1055/s-0031-1273690
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility and Dance: A Review

Abstract: Joint hypermobility is defined as an excessive range of motion. Although the dance profession has often promoted hypermobility for aesthetic reasons, there is a belief amongst health professionals that potential risks associated with the condition may have been overlooked. The aims of this review were to examine the epidemiology of joint hypermobility in dancers; the effects on fatigue and bone health; the injury profile of hypermobile dancers; and the use of the Beighton score as a diagnostic tool. Depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 73 publications
(47 reference statements)
2
41
2
7
Order By: Relevance
“…GJH is often diagnosed using the Beighton score (see also “Measurement properties of existing clinical assessment methods for local and generalized joint hypermobility—a systematic review,” Juul‐Kristensen et al, this issue), although this has major limitations in selected populations, such as the very young and the elderly [Dolan et al, ; Castori, ]. It can be asymptomatic, and is more common among dancers and elite athletes where it may confer a constitutional advantage [Day et al, ; Beighton et al, ]; however, it may predispose to higher injury rates [Briggs et al, ; Konopinski et al, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…GJH is often diagnosed using the Beighton score (see also “Measurement properties of existing clinical assessment methods for local and generalized joint hypermobility—a systematic review,” Juul‐Kristensen et al, this issue), although this has major limitations in selected populations, such as the very young and the elderly [Dolan et al, ; Castori, ]. It can be asymptomatic, and is more common among dancers and elite athletes where it may confer a constitutional advantage [Day et al, ; Beighton et al, ]; however, it may predispose to higher injury rates [Briggs et al, ; Konopinski et al, ].…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Not all individuals with GJH are symptomatic, some even take advantage of GJH and excel in certain sports like gymnastics, martial arts or dancing [11,12]. Others experience mild to severe musculoskeletal complaints [13], like joint pain in multiple joints [10], fatigue [13], diminished motor competence [14] and muscle weakness [15].…”
Section: Introductionmentioning
confidence: 99%
“…36 Within the general population of schoolchildren aged 14 years, GJH (cut point, 4/9) prevalence of 11% to 28% has been reported. 4 Some studies have reported a high prevalence of GJH for certain disciplines, such as dancing and ballet, 7,30 possibly due to the great requirements of flexibility in these activities. 30 However, no study has reported the prevalence of GJH in elite-level adolescent athletes for sports such as team handball, TeamGym gymnastics, as well as ballet.…”
mentioning
confidence: 99%